The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1744806916629065
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of neurochemically defined excitatory interneuron populations in laminae I–III of the mouse spinal cord

Abstract: BackgroundExcitatory interneurons account for the majority of neurons in laminae I–III, but their functions are poorly understood. Several neurochemical markers are largely restricted to excitatory interneuron populations, but we have limited knowledge about the size of these populations or their overlap. The present study was designed to investigate this issue by quantifying the neuronal populations that express somatostatin (SST), neurokinin B (NKB), neurotensin, gastrin-releasing peptide (GRP) and the γ iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
121
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(133 citation statements)
references
References 88 publications
(205 reference statements)
12
121
0
Order By: Relevance
“…Because we had previously found that many neurotensin‐expressing cells also showed moderate‐strong labeling for PKCγ (Gutierrez‐Mecinas et al, ), we examined the relationship between neurotensin and CCK among PKCγ‐expressing cells. For this analysis, we excluded cells that showed weak PKCγ‐immunoreactivity, because we have reported that many of these are PPTB‐immunoreactive (Gutierrez‐Mecinas et al, ), and PPTB shows minimal coexpression with either CCK or neurotensin. We identified a total of 838 cells with moderate‐strong PKCγ‐immunoreactivity in sections from three mice, and found that 44% of these were pro‐CCK+ only, 40% were neurotensin+ only, while 2% had both types of peptide immunoreactivity, and 15% had neither (Figure a–d,h).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because we had previously found that many neurotensin‐expressing cells also showed moderate‐strong labeling for PKCγ (Gutierrez‐Mecinas et al, ), we examined the relationship between neurotensin and CCK among PKCγ‐expressing cells. For this analysis, we excluded cells that showed weak PKCγ‐immunoreactivity, because we have reported that many of these are PPTB‐immunoreactive (Gutierrez‐Mecinas et al, ), and PPTB shows minimal coexpression with either CCK or neurotensin. We identified a total of 838 cells with moderate‐strong PKCγ‐immunoreactivity in sections from three mice, and found that 44% of these were pro‐CCK+ only, 40% were neurotensin+ only, while 2% had both types of peptide immunoreactivity, and 15% had neither (Figure a–d,h).…”
Section: Resultsmentioning
confidence: 99%
“…We had previously shown that many of the cells with moderate‐strong PKCγ immunoreactivity contained neurotensin (Gutierrez‐Mecinas et al, ). Although PPTB cells were often PKCγ‐positive, the level of PKCγ in these cells was generally much lower, and they may therefore not contribute significantly to the allodynia attributed to PKCγ, or to PKCγ‐expressing neurons.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The origin of the excitatory calretinin population is mixed because most, but not all cells are derived from the Lbx1 lineage (Duan et al, 2014;Peirs et al, 2015). The SOM + population makes up a large proportion (∼59%) of the excitatory interneurons in lamina II (Gutierrez-Mecinas et al, 2016). Those residing at the lamina II/III border overlap with PKCγ neurons, a population also implicated in mechanical allodynia (Malmberg et al, 1997;Petitjean et al, 2015).…”
Section: Pain Temperature and Itchmentioning
confidence: 99%
“…This is especially reflected for example by the lamina specific innervation pattern by the different types of peripheral sensory neurons: unmyelinated C fibers, which mainly carry noxious and thermal information, terminate in the superficial dorsal horn (laminae I-II), while thickly myelinated Ab fibers, which convey innocuous signals including touch and proprioceptive information, terminate in the deep dorsal horn (laminae III-V) [3,6,7]. A laminar organization of neuronal function is also supported by gene expression patterns that follow laminar patterns [8][9][10][11][12]. Furthermore, optogenetic and chemogenetic experiments support a modality-specific processing by distinct genetically defined neuron populations [7,[13][14][15].…”
mentioning
confidence: 99%